ANALISIS PASAL 41 HINGGA PASAL 46 PERDA KOTA BUKITTINGGI NOMOR 02 TAHUN 2024 TENTANG KETENTRAMAN KETERTIBAN UMUM(STUDI TAFSIR MAQASHIDI DAN AL-QUR'AN) - Chandra Kirana; Muhammad Taufiq (Adisam Publisher, 2025)
The rise of social disease, namely sexual deviation, which occurs in the city of Bukittinggi, is a major factor in the city of Bukittinggi, where the philosophy of life of the Minangkabau people, especially the city of Bukittinggi, is